MENCARI BAHAGIA DI PESANTREN: PERAN KEBERSYUKURAN TERHADAP SUBJECTIVE WELL-BEING PADA SANTRI - Haq, Muhammad Shodikul; Hanifah, Raidah (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to examine the relationship between gratitude and subjective well-being among adolescent students (santri) in Islamic boarding schools. The research employed a quantitative correlational method with a sample of 90 junior high school-level santri (MTs) from an Islamic boarding school in Yogyakarta. The instruments used were the subjective well-being scale and the gratitude scale, both of which had been tested for validity and reliability. Data were analyzed using the Pearson Product Moment correlation technique. The results showed a significant positive relationship between gratitude and subjective well-being, with a correlation coefficient of r = 0.425 and a significance value of p = 0.031. This indicates that the higher the level of gratitude experienced by santri, the higher their level of subjective well-being. The findings suggest that gratitude is an important internal factor that can serve as a psychological protector for adolescent santri in dealing with the pressures of boarding school life. The implication of this study highlights the importance of integrating gratitude-based values into character development programs and psychological interventions within Islamic boarding school environments. ABSTRAKPenelitian ini bertujuan untuk mengetahui hubungan antara kebersyukuran dan subjective well-being pada santri. Penelitian menggunakan metode kuantitatif korelasional dengan sampel sebanyak 90 santri MTs di salah satu pondok pesantren di Yogyakarta. Instrumen yang digunakan adalah skala subjective well-being dan skala kebersyukuran, yang telah diuji validitas dan reliabilitasnya. Data dianalisis menggunakan teknik korelasi Pearson Product Moment. Hasil penelitian menunjukkan adanya hubungan positif yang signifikan antara kebersyukuran dan subjective well-being dengan nilai r = 0,425 dan p = 0,031. Artinya, semakin tinggi rasa syukur yang dimiliki santri, semakin tinggi pula tingkat kesejahteraan subjektifnya. Simpulan dari penelitian ini menunjukkan bahwa kebersyukuran merupakan salah satu faktor penting yang dapat berperan sebagai protektor psikologis bagi remaja santri dalam menghadapi tekanan kehidupan pesantren. Implikasi dari temuan ini adalah pentingnya penguatan nilai syukur dalam program pembinaan karakter dan intervensi psikologis di lingkungan pesantren.